Phase 1 Study of the Effects of the Tuberculosis Treatment Pretomanid, Alone and in Combination With Moxifloxacin, on the QTc Interval in Healthy Volunteers. Issue 6 (30th December 2020) - Li, Mengchun; Saviolakis, George A.; El‐Amin, Wael; Makhene, Mamodikoe K.; Osborn, Blaire; Nedelman, Jerry; Yang, Tian J.; Everitt, Daniel
Abstract: Tuberculosis (TB) continues to be a serious threat to public health throughout the world. Newer treatments are needed that could offer simplified regimens with activity against both drug‐sensitive and drug‐resistant bacilli, while optimizing safety. Pretomanid (PA‐824), a nitroimidazooxazine compound, is a new drug for the treatment of pulmonary TB that was recently approved in the United States and Europe in the context of a regimen combined with bedaquiline and linezolid. This phase 1 double‐blind, randomized, placebo‐controlled crossover study specifically examined the effect of single‐dose administration of pretomanid 400 or 1000 mg and pretomanid 400 mg plus moxifloxacin 400 mg on the QTc interval in 74 healthy subjects. Subjects were fasting at the time of drug administration. Pretomanid concentrations following single 400‐ or 1000‐mg doses were not associated with any QT interval prolongation of clinical concern. Moxifloxacin did not alter the pharmacokinetics of pretomanid, and the effect of pretomanid 400 mg plus moxifloxacin 400 mg on the individually corrected QT interval was consistent with the effect of moxifloxacin alone. Both drugs were generally well tolerated. Although supratherapeutic exposure of pretomanid relative to the now‐recommended dosing with food was not achieved, these findings contribute to the favorable assessment of cardiac safety for pretomanid.